Eternal Kaveri historical sites along South India's greatest river - Michell, George; Arni, Clare; National Centre for the Performing Arts (India). (Mumbai Published by J.J. Bhabha for Marg Publications on behalf of the National Centre for the Performing Arts, 1999)
Description of historic places through which Cauvery River, India flows.
"Marg Publications."
Keywords: Historic sites -- India -- Cauvery River Valley; Cauvery River Valley (India) -- Description and travel; Cauvery River Valley (India) -- Pictorial works